Color model environments : color and light in three-dimensional design - Linton, Harold; Rochon, Richard (New York : Van Nostrand Reinhold Company, Inc., 1985)
Color Model Environments is a timely and important landmark because of its major contribution to the interdisciplinary design dialogue. Its central purpose is threefold: to present a structural order underlying the effective use of color and light; to communicate this order based on three-dimensional design principles; and to relate these aspects to the planning stages and concepts for model forms used by students and professionals in several design disciplines.
Foreword -- Preface -- Acknowledgments -- 1. The elements of design -- 2. Materials, methods, and techniques -- 3. Composition, light and movement -- 4. Color structure and design -- 5. The response of form and pigment to light -- 6. Principles of color and design -- 7. Columns, planes, and wall structures in color and light -- 8. Studies of mass in color and light -- 9. Enclosure and volume -- 10. Expressive dimensions -- Appendix 1 -- Appendix 2 -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: COLOR IN ARCHITECTURE